Calorimetric Determination of the Heat of Detonation of Commercial Explosives - P D. Katsabanis; Q Liu (International Society of Explosives Engineers, 1993)
The energy output of crushed AN/FO, crushed AN/FO mixed with Aluminum (5%, 6.4% and 9.4% A1 by mass) and a commercial emulsion explosive has been measured using a detonation calorimeter. The charges had a diameter of 10 mm and were heavily confined by a 11 mm thick copper shell. In order to achieve stable detonation glass microballoons were used in the explosives so that the density of the AN/FO charges would be around 1.1 g/cc. The charges were detonated in vacuum and the detonation products were analyzed using gas chromatography. It was found that energy values were very close to calculated values obtained by ideal detonation codes.